Assessing construction and demolishing debris usage in the Ghanaian construction industry - Asah, Emmanuel (2021)
A thesis submitted to the Department of Construction Technology and Management, College of Art and Built Environment, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the Award Degree of Master of science in construction management.